Motor Unit Properties of the First Dorsal Interosseous in Chronic Stroke Subjects: Concentric Needle and Single Fiber EMG Analysis - Yao, Bo; Klein, Cliff S.; Hu, Huijing; Li, Sheng; Zhou, Ping (Frontiers in Physiology, 2018)
Concentric needle electromyography (EMG) and single fiber EMG were applied to assess electrophysiological signs of changes in the motor units after stroke. The first dorsal interosseous (FDI) muscle was studied bilaterally in eleven hemiparetic stroke subjects. The main outcome was compared between the paretic and contralateral sides of all stroke subjects. A significant increase in fiber density was found in the paretic muscle compared with the contralateral side. No statistically significant difference was found between the paretic and contralateral sides in most motor unit action potential (MUAP) parameters and jitter. The result of single fiber EMG, in conjunction with concentric needle EMG, in the FDI muscle supports the possible collateral reinnervation and architecture change of the motor units in post-stroke subjects. However, the sprouting might be insufficient to result in a statistically significant change in the MUAP parameters. Single fiber EMG appears more sensitive than concentric needle EMG to reflect muscle structure and electrophysiological signs of changes in the motor units after stroke. The combination of single fiber EMG and concentric needle EMG could provide supplementary information and be helpful to assess the paretic muscle changes after stroke.